2009
DOI: 10.2967/jnumed.109.063396
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aggressive Primary Prostate Cancer with 11C-Choline PET/CT Using Multimodality Fusion Techniques

Abstract: The aim of the study was to assess whether 11 C-choline PET/CT could identify high-risk primary adenocarcinoma of the prostate. Methods: 11 C-choline PET/CT and transpelvic MRI were performed in 14 patients with untreated localized primary adenocarcinoma of the prostate, followed by radical prostatectomy as a form of primary monotherapy within 14 d of in vivo imaging. To allow accurate coregistration of whole-mount histology with in vivo imaging, additional ex vivo MR images of the prostatectomy specimen were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 31 publications
4
75
0
3
Order By: Relevance
“…PET imaging parameters showed significant correlations with PSA level, and both MTV and PSA level were significant predictors of distant metastasis. However, the maximum SUV, mean SUV, MTV, and UVP did not show a correlation with the Gleason score, as previous studies indicated [9,15]. Further, we included texture-based quantification in our study to determine whether tumor metabolic heterogeneity was correlated with the Gleason score.…”
Section: Discussionmentioning
confidence: 88%
“…PET imaging parameters showed significant correlations with PSA level, and both MTV and PSA level were significant predictors of distant metastasis. However, the maximum SUV, mean SUV, MTV, and UVP did not show a correlation with the Gleason score, as previous studies indicated [9,15]. Further, we included texture-based quantification in our study to determine whether tumor metabolic heterogeneity was correlated with the Gleason score.…”
Section: Discussionmentioning
confidence: 88%
“…11 C-choline and 18 F-fluorocholine are widely used PET radiotracers for prostate cancer imaging (9,20), but also 11 C-methionine and 11 C-acetate PET have been successfully tested for this indication (32,33). 11 C-choline is known to be rapidly transported into human cancers, including prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 C-choline and 18 F-fluorocholine are widely used PET radiopharmaceuticals for imaging of prostate cancer, particularly in the setting of prostate cancer recurrence (7). At primary staging, 11 C-choline preferentially identifies intermediateand high-risk (i.e., clinically significant) prostate cancer, whereas low-risk lesions are typically not visualized (8,9). However, choline radiotracers are limited because of commonly observed increased retention in nodular benign prostatic hyperplasia (10) as well as unsatisfactory accuracy for nodal metastatic disease in initial staging (11).…”
mentioning
confidence: 99%
“…Also, lesion detection by anatomical MRI increases with Gleason grade, favouring detection of more aggressive disease stages even when lesion size is small [21]. On the other hand, the metabolic signature of lesions identified by 11 C-choline PET may also have prognostic value related to cancer aggressiveness [22]. Thus one would hope that the combination of both as a single examination (without the need for image fusion) may improve clinical staging by aiding in the identification of significant disease earlier than possible with MRI or PET/CT alone.…”
Section: Mri and Pet/mrmentioning
confidence: 99%